Management Status of Agricultural Plant Genetic Resources in Nepal - Paudel, M N; Joshi, B K; Ghimire, K H (Agronomy Journal of Nepal, 2016)
Agricultural plant genetic resources (APGRs) are one of the pivotal sources for developing high yielding, stress tolerance varieties to sustain food and nutritional security of the world. Nepal has established National Agriculture Genetic Resource Centre (NAGRC), alias Genebank under the Nepal Agricultural Research Council (NARC) in Khumaltar premise in 2010 AD (2066 BS). NAGRC has been doing collection, identification, characterization, and regeneration of APGRs since its establishment. There are more than 11000 collections of APGRs in the Genebank. These accessions include cereals, pseudo cereals, pulses, oilseeds and vegetable of orthodox seed whereas crops having recalcitrant seed are conserved in the field Genebank, on-farm genebank and tissue bank. To analyze characters of new accessions, standard passport data are recorded and entered to accessions giving geographical locations and coordinates. The APGRs have been collected, cleaned, processed, preserved and regenerated and characterized according to the standard procedures and norms used by scientists across the world. Types of Genebank and options for effective management of APGRs in Nepal have explained in brief. This paper tries to explain the importance and management of APGRs with respect to sustain food and nutritional security of Nepal in coming days ahead.Agronomy Journal of Nepal (Agron JN) vol. 4, 2016, Page: 75-91